2021
DOI: 10.3390/info12030127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Consumers’ Willingness to Pay for Delay Compensation Services in Intra-City Delivery—A Value Optimization Study Using Choice

Abstract: Intra-city delivery has developed rapidly along with the expansion of the logistics industry. Timely delivery is one of the main requirements of consumers and has become a major challenge to delivery service providers. To compensate for the adverse effects of delivery delays, platforms have launched delay compensation services for consumers who order. This study quantitatively evaluated consumer perception of the delay compensation service in intra-city deliveries using a choice experiment. We explored how dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Ref. [4] evaluate the willingness to pay for the compensation service in case of delayed delivery in China. They conduct a discrete choice experiment where individuals are presented with a form with 6 sheets.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [4] evaluate the willingness to pay for the compensation service in case of delayed delivery in China. They conduct a discrete choice experiment where individuals are presented with a form with 6 sheets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, this paper investigates whether there is a relationship between socio-demographic characteristics and the attributes of the delivery service. Building on the works of [3,4], we conducted a Discrete Choice Experiment (DCE). For this purpose, we designed a survey and applied it to 424 consumers in the city of Santiago, Chile.…”
Section: Introductionmentioning
confidence: 99%
“…According to Pan et al (2021), the increase in the rate of ordering food using the platform showed that the speed in the delivery of ordered food, payments on time (debts), and discounts when payments were made in cash were some of the things that platform or app users want. Alalwan (2020) adds that what has been researched in Jordan related to the interest in reusing food order applications is caused by online reviews, online ratings, real-time driver position tracking, hedonic motivation, food prices, and expectations of the speed of food arrivals at the end of the year.…”
Section: Introductionmentioning
confidence: 99%